Disability, Economic Globalization and Privatization: A Case Study of India - Vanmala Hiranandani; Deepa Sonpal (Disability Studies Quarterly, 2010)
<!--[if gte mso 9]> <![endif]--><!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--> <!-- /* Font Definitions */ @font-face {font-family:"Cambria Math"; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:0; mso-generic-font-family:roman; mso-font-pitch:variable; mso-font-signature:-1610611985 1107304683 0 0 159 0;} @font-face {font-family:Calibri; panose-1:2 15 5 2 2 2 4 3 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:-1610611985 1073750139 0 0 159 0;} /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin-top:0in; margin-right:0in; margin-bottom:10.0pt; margin-left:0in; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-fareast-font-family:"Times New Roman"; mso-bidi-font-family:"Times New Roman";} p.Default, li.Default, div.Default {mso-style-name:Default; mso-style-unhide:no; mso-style-parent:""; margin:0in; margin-bottom:.0001pt; mso-pagination:widow-orphan; mso-layout-grid-align:none; text-autospace:none; font-size:12.0pt; font-family:"Times New Roman","serif"; mso-fareast-font-family:"Times New Roman"; color:black;} .MsoChpDefault {mso-style-type:export-only; mso-default-props:yes; font-size:10.0pt; mso-ansi-font-size:10.0pt; mso-bidi-font-size:10.0pt; mso-ascii-font-family:Calibri; mso-hansi-font-family:Calibri;} @page Section1 {size:8.5in 11.0in; margin:1.0in 1.0in 1.0in 1.0in; mso-header-margin:.5in; mso-footer-margin:.5in; mso-paper-source:0;} div.Section1 {page:Section1;} /* List Definitions */ @list l0 {mso-list-id:-1640387735; mso-list-type:hybrid; mso-list-template-ids:-127898260 -1 -1 -1 -1 -1 -1 -1 -1 -1;} @list l0:level1 {mso-level-suffix:none; mso-level-text:""; mso-level-tab-stop:none; mso-level-number-position:left; margin-left:0in; text-indent:0in;} @list l0:level2 {mso-level-start-at:0; mso-level-text:""; mso-level-tab-stop:none; mso-level-number-position:left; margin-left:0in; text-indent:0in;} @list l0:level3 {mso-level-start-at:0; mso-level-text:""; mso-level-tab-stop:none; mso-level-number-position:left; margin-left:0in; text-indent:0in;} @list l0:level4 {mso-level-start-at:0; mso-level-text:""; mso-level-tab-stop:none; mso-level-number-position:left; margin-left:0in; text-indent:0in;} @list l0:level5 {mso-level-start-at:0; mso-level-text:""; mso-level-tab-stop:none; mso-level-number-position:left; margin-left:0in; text-indent:0in;} @list l0:level6 {mso-level-start-at:0; mso-level-text:""; mso-level-tab-stop:none; mso-level-number-position:left; margin-left:0in; text-indent:0in;} @list l0:level7 {mso-level-start-at:0; mso-level-text:""; mso-level-tab-stop:none; mso-level-number-position:left; margin-left:0in; text-indent:0in;} @list l0:level8 {mso-level-start-at:0; mso-level-text:""; mso-level-tab-stop:none; mso-level-number-position:left; margin-left:0in; text-indent:0in;} @list l0:level9 {mso-level-start-at:0; mso-level-text:""; mso-level-tab-stop:none; mso-level-number-position:left; margin-left:0in; text-indent:0in;} ol {margin-bottom:0in;} ul {margin-bottom:0in;} --> <!--[if gte mso 10]> <![endif]--> <!--[if !supportLists]--> <!--[endif]-->People with disabilities are one of the most disenfranchised groups in India. Standardized measurements of disability in India and internationally have overlooked the linkages between the economy and disability. In recent decades, neo-liberal economic reforms imposed in developing countries, under pressure from international financial institutions, have downsized state role, privatized social goods, and encouraged export-led strategies and market-based economics. India’s economic reforms, initiated in 1991, have led to rapid economic growth that is, however, increasingly mal-distributed. <!--[if !supportLists]--> <!--[endif]-->This paper investigates the implications of economic restructuring in the arenas of social programs, education, employment, accessibility, health, agriculture and food security, and water and land acquisition from a disability perspective. Our analysis shows that while increased employment opportunities and accessibility have benefitted middle-class and highly-skilled disabled persons, the majority of people with disabilities have been left out of India’s economic affluence. We contend that India’s globalized economy and reduced state role necessitate renewed understanding of human rights, including disability rights.
Keywords: disability; privatization; India-economic reforms; international development